Polymorphisms in ATP-binding cassette transporters associated with maternal methylmercury disposition and infant neurodevelopment in mother-infant pairs in the Seychelles Child Development Study. (September 2016) - Engström, Karin; Love, Tanzy M.; Watson, Gene E.; Zareba, Grazyna; Yeates, Alison; Wahlberg, Karin; Alhamdow, Ayman; Thurston, Sally W.; Mulhern, Maria; McSorley, Emeir M.; Strain, J.J.; Davidson, Philip W.; et al.
Abstract: Background: ATP-binding cassette (ABC) transporters have been associated with methylmercury (MeHg) toxicity in experimental animal models. Aims: To evaluate the association of single nucleotide polymorphisms (SNPs) in maternal ABC transporter genes with 1) maternal hair MeHg concentrations during pregnancy and 2) child neurodevelopmental outcomes. Materials and methods: Nutrition Cohort 2 (NC2) is an observational mother-child cohort recruited in the Republic of Seychelles from 2008–2011. Total mercury (Hg) was measured in maternal hair growing during pregnancy as a biomarker for prenatal MeHg exposure (N = 1313) (mean 3.9 ppm). Infants completed developmental assessments by Bayley Scales of Infant Development II (BSID-II) at 20 months of age (N = 1331). Genotyping for fifteen SNPs in ABCC1, ABCC2 and ABCB1 was performed for the mothers. Results: Seven of fifteen ABC SNPs ( ABCC1 rs11075290, rs212093, and rs215088; ABCC2 rs717620; ABCB1 rs10276499, rs1202169, and rs2032582) were associated with concentrations of maternal hair Hg (p < 0.001 to 0.013). One SNP ( ABCC1 rs11075290) was also significantly associated with neurodevelopment; children born to mothers with rs11075290 CC genotype (mean hair Hg 3.6 ppm) scored on average 2 points lower on the Mental Development Index (MDI) and 3 points lower on the Psychomotor Development Index (PDI) than children born to mothers with TT genotype (mean hair Hg 4.7 ppm) while children with the CT genotype (mean hair Hg 4.0 ppm) had intermediate BSID scores. Discussion: Genetic variation in ABC transporter genes was associated with maternal hair Hg concentrations. The implications for MeHg dose in the developing child and neurodevelopmental outcomes need to be further investigated. Highlights: SNPs in three ABC transporter genes were associated with hair mercury in mothers. Maternal ABCC1 SNP rs11075290 was associated with child neurodevelopment. Genetics of ABC may determine prenatal methylmercury concentrations.